Electrospun fibers based on botanical, seaweed, microbial, and animal sourced biomacromolecules and their multidimensional applications - Akshay Kumar, K P; Zare, Ehsan Nazarzadeh; Torres-Mendieta, Rafael; Wacławek, Stanisław; Makvandi, Pooyan; Černík, Miroslav; Padil, Vinod V T; Varma, Rajender S (International journal of biological macromolecules, 2021)
This review summarizes and broadly classifies all of the major sustainable natural carbohydrate bio-macromolecular manifestations in nature - from botanical (cellulose, starch, and pectin), seaweed (alginate, carrageenan, and agar), microbial (bacterial cellulose, dextran, and pullulan), and animal (hyaluronan, heparin, chitin, and chitosan) sources - that have been contrived into electrospun fibers. Furthermore, a relative study of these biomaterials for the fabrication of nanofibers by electrospinning and their characteristics viz. solution behavior, blending nature, as well as rheological and fiber attributes are discussed. The potential multidimensional applications of nanofibers (filtration, antimicrobial, biosensor, gas sensor, energy storage, catalytic, and tissue engineering) originating from these polysaccharides and their major impacts on the properties, functionalities, and uses of these electrospun fibers are compared and critically examined.
Keywords: Multidimensional applications; celulosa; Tissue Engineering; Heparin; škrob; Alginates; glukany; Carrageenan; Dextrans; Hyaluronic Acid; chitin; Agar; karagenan; Cellulose; Electrochemical Techniques; agar; elektrochemické techniky; tkáňové inženýrství; Chitosan; Animals; Biocompatible Materials; lidé; biokompatibilní materiály; nanovlákna; pektiny; Chitin; chitosan; algináty; Glucans; Humans; zvířata; Nanotechnology; dextrany; Nanofibers; Electrospinning of bio-macromolecules; Pectins; Starch; Fiber morphology and structures; heparin; kyselina hyaluronová; nanotechnologie